2021
DOI: 10.2147/ott.s328839
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Complete Response to Gefitinib in a Patient with SqCLC Harboring EGFR p.E746_S752delinsV Mutation

Abstract: Development of targeted therapies for squamous cell lung cancer (SqCLC) is currently limited by the prevalence of activating mutations and their predicting power of treatment efficacy. In the present study, we describe a case of treatment-naïve stage IIIB SqCLC that harbored a rare epidermal growth factor receptor (EGFR) p.E746_S752delinsV mutation with clinical complete response to neoadjuvant gefitinib. Pathological complete response was confirmed after surgical resection. No disease recurrence was documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Giuseppina Improta et al reported the TKI sensitivity in a small cohort of lung adenocarcinomas bearing uncommon exon 19 mutations, Which described two advanced LADC patients with EGFR p.L747_T751delinsP mutation and p.T751_I759delinsS respectively who have only 2-month PFS on gefitinib therapy (22). However, an IIIB Squamous cell lung cancer (SqCLC) patient harboring EGFR Exon 19 E746_S752delinsV mutation could benefit from targeted therapies of gefitinib, and no evidence of disease was found for up to 20 months, which indicated that the first-generation EGFR TKIs might be a good choice for advanced SqCLC patients and different types of uncommon exon 19 mutations have a different response to TKIs (23). Besides, Robichaux et al described an approach that separated the EGFR mutations into four subgroups based on structure-function and to predict the EGFR TKIs sensitivity for uncommon EGFR mutations (6).…”
Section: Discussionmentioning
confidence: 99%
“…Giuseppina Improta et al reported the TKI sensitivity in a small cohort of lung adenocarcinomas bearing uncommon exon 19 mutations, Which described two advanced LADC patients with EGFR p.L747_T751delinsP mutation and p.T751_I759delinsS respectively who have only 2-month PFS on gefitinib therapy (22). However, an IIIB Squamous cell lung cancer (SqCLC) patient harboring EGFR Exon 19 E746_S752delinsV mutation could benefit from targeted therapies of gefitinib, and no evidence of disease was found for up to 20 months, which indicated that the first-generation EGFR TKIs might be a good choice for advanced SqCLC patients and different types of uncommon exon 19 mutations have a different response to TKIs (23). Besides, Robichaux et al described an approach that separated the EGFR mutations into four subgroups based on structure-function and to predict the EGFR TKIs sensitivity for uncommon EGFR mutations (6).…”
Section: Discussionmentioning
confidence: 99%